ANALISIS PENINGKATAN KUALITAS PELAYANAN BONGKAR MUAT BARANG DI PELABUHAN PROBOLINGGO (Studi Kasus PT Delta Arta Bahari Nusantara Cabang Probolinggo) - Ardhian Trilaksono; Indung Sudarso (Universitas Putera Batam, 2021)
PT Delta Arta Bahari Nusantara is a regional-owned company owned by the East Java region as a loading and unloading operator for the Probolinggo port trying to improve port operation services, one of the efforts that has been made is building port facilities. There is an increase in loading and unloading activities of superior commodities, it is necessary to increase the quality. Efforts to maintain service quality of a company must analyze and serve data and information accordingly from data and measurements, in this case, product suitability and customer satisfaction levels. The purpose of this research is to measure the service quality of PT Delta Arta Bahari Nusantara uses 5 service quality dimensions, the measurement results (gap) between customer perceptions and expectations are evaluated by the Quality Function Deployment (QFD) method. Furthermore, based on the policy (gap) and QFD, strategies are formulated that must be carried out. The results of the analysis showed that all dimensions resulted in a satisfaction level of